English Vocabulary in the Mind of Student - Suharyanto H Soro (International Journal of Nusantara Islam, 2019)
Lecturer plays an important role in teaching Englishas a foreign language, in spite of the success of teaching English itself depends on the many factors, one of them is students’ participation in the English class. In the other words, the teaching of English becomes useful and more systematically when the lecturer is fully aware of the aims and values of teaching of English subject since the core principle of any teaching  is “know what you do and only do what you know”. Hence it is essential to understand the aims and values of teaching English. In linguistics study,performance and competence are different, competence is study about language rules in the abstract form or one’s capacity to use a language, while performance is the application of one’s ability in the concrete form, or the actual application of this competence in speaking or listening. Chomsky (1965:18) said that  performance is the effect or the application of competence. Further he said that clearly, the actual data of linguistic performance will provide much evidence for determining the correctness of hypotheses about underlining linguistic structure. Notice the following figure. The data collection procedures in the present study are based on classroom participant observation, student interviews, and questionnaire  are the primary sources of data collection. As a point of departure, unstructured interviews conducted with English and students to gain initial understanding of the learning English as a foreign language. This also serves as a pilot study, paving the way for designing the guidelines for the semi structured individual interviews. Notes taken in these unstructured interviews were included in the data analysis. Taking lecture involves the lecturer and the students in formal setting. Lecturer is one who transfers special knowledge (English teaching materials) to his students in form of academic setting. They are engaged in academic norms, for example lecturer has qualified education (magister or doctorate degree) and the students  have already registered their status as a university student. The lecturer’s function is threefold. In the presentation stage of the material, the lecturer serves as a model, setting up situations in which the need for the target structure is created and modeling the new structure for students to repeat. The lecturer was required to be skillful manipulator, using questions, commands, and other cues to elicit correct sentences from the students. The students wanted the lecturer to give more opportunities for English practice. They can learn from mistakes and develop in real situation. Role play is one of methods can be applied in teaching English. The students like this methods (96%) because they can imitate and practice their English pronunciation.